Attributes of soil quality indicators in area under direct plantingto twelve years - Torres, José Luiz Rodrigues; Souza, Zigomar Menezes de; Pereira, Marcos Gervasio; Assis, Renato Lara de (Comunicata Scientiae, 2015)
The relationship between management and soil quality systems can be evaluated through the changes in their physical attributes and quantified through soil quality indicators. In this study we evaluated changes in soil physical properties after twelve-tillage in the Savanna, Brazil. The design was randomized blocks, where they were evaluated five covers soil (sun hemp, millet, sorghum, Brachiaria and fallow), evaluated in two seasons (2002 and 2012). The aggregate stability (SA), mean weighted diameter was evaluated (MWD), geometric (MWG), aggregate stability indices (ISA), sensitivity (Is) and the percentage of aggregates of a diameter greater than 2 mm (AGRI), mechanical resistance to penetration (RP), bulk density (Ds) and water content (UV), with four repetitions. The best soil aggregation indices of areas with sorghum coverage; EA in the area increased after ten years of no tillage; The increase of the Ds in the deeper layers caused the decrease of the MW and MWG and confirmed the effect of this parameter SA in the soil; Significant correlations of Ds with the other parameters showed the importance of this attribute as soil quality indicator; In 2012 it was found the soil compaction in all treatments in the depth of 0.30 m.